En kartläggning kring användandet av köldmedier ombord på svenska fartyg - Hansson, John; Ghavampouri, Ali (My University, 2014)
In most refrigerators and AC units, there is some type of refrigerant. In the 80’s scientists discovered that CFC- and HCFC-based refrigerants (CFCs and HCFCs) had negative effects on the ozone layer. These negative characteristics are the breakdown of the vital ozone layer. The discovery led to a need to regulate the use of these gases, and the first international agreement was the Montreal Protocol in 1987. The F-Gas regulation stated that CFC substances must not be used from 2000 and those HCFCs must not be replenished from 2002 and will be banned from 2015. This work identifies how the ban of CFC-based refrigerants and the replenishment stop of HCFC-based substances have influenced Swedish ships. As a support in our work, we have studied all the control and conversion reports of refrigerants from Swedish ships during the years 2007-2012. All Swedish flagged vessels must submit such annual reports to the Transport Agency. The reports from the Transport Agency have been compiled into a variety of charts, to identify the amounts of R22 and how HFC substances are used on board vessels. The amount of R22 decreased between each year and was available only in a limited quantity in 2012. It could also be identified what type of refrigerant was used in most freezers, refrigerators and air conditioners. In addition to the control and conversion reports, we also had access to a number of leakage reports; these were compiled to create an impression of the magnitude of refrigerant leakage from ships.
Keywords: Annan teknik; Transport; Other Engineering and Technologies; Transport